PERAWATAN GIGI DAN MULUT PADA ANAK RETARDASI MENTAL (Studi Pustaka) - Margaretha Suharsini (Faculty of Dentistry, Universitas Indonesia, 2015)
Periodontal disease, dentla caries and malocclusion are frequently found in mentally retarded children. The frequency of these diseases are higher than normal children. The condition of mental retardation makes these children difficult to care for their oral hygiene. Basically there is no difference of treatment for mentally retarded children compared to normal children. Dentists should have certain sills to treat the these special children, especially in behavior management. Preventive care and behavior management are the most important considerations in achieving a successful treatment.